If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.6t + 7 = -8 Reorder the terms: 7 + 0.6t = -8 Solving 7 + 0.6t = -8 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 0.6t = -8 + -7 Combine like terms: 7 + -7 = 0 0 + 0.6t = -8 + -7 0.6t = -8 + -7 Combine like terms: -8 + -7 = -15 0.6t = -15 Divide each side by '0.6'. t = -25 Simplifying t = -25
| 32+-1t=-1 | | -3-4m+9m=12 | | T-(-5)=5 | | 3(X-3)(X-1)(X-4)+2(X-2)(X-1)(X-4)-4(X-2)(X-3)(X-4)-1(X-2)(X-3)(X-1)=0 | | 3(4y-3)-4=4(5y-6)+7 | | 32-t=-1 | | 15-4x+17=12 | | 5.910-1.708= | | 6(2x+2)=-22 | | 8F-3-6=8f-3f+2+4 | | 3x+y^2=4 | | 4(y+4)=2(y+3) | | w^3-8= | | 5.91-1.708= | | 6n-1+18=4 | | 4x+3y+2=7x+14 | | 3(4g+6)=2(6g+g) | | 3x+6-2x=7+2x-5 | | .2x-.8x-47=1 | | 3c-4c=5c-3c+2 | | 2t-5=6y-1 | | 6k+10=110 | | 1n-7n=18 | | 5y-7=-13i | | (x^3+6x^2-4x+7)-(3x^2+2x-4)= | | 9(a-4)+2(a-20)=a-11 | | u-3=-5u+13 | | 5x+6x-8x=6+6 | | x+x-20=100 | | -4*(x-7)=2x+4 | | 5z-3=2z+12 | | 6*19= |